HMGB1 Promotes Myeloid Egress and Limits Lymphatic Clearance of Malignant Pleural Effusions - Soloff, Adam C.; Jones, Katherine E.; Powers, Amy A.; Murthy, Pranav; Wang, Yue; Russell, Kira L.; Byrne-Steele, Miranda; Lund, Amanda W.; Yuan, Jian-Min; Monaco, Sara E.; Han, Jian; Dhupar, Rajeev; et al. (Frontiers in Immunology, 2020)
Pleural effusions, when benign, are attributed to cardiac events and suffusion of fluid within the pleural space. When malignant, lymphatic obstruction by tumor and failure to absorb constitutively produced fluid is the predominant formulation. The prevailing view has been challenged recently, namely that the lymphatics are only passive vessels, carrying antigenic fluid to secondary lymphoid sites. Rather, lymphatic vessels can be a selective barrier, efficiently coordinating egress of immune cells and factors within tissues, limiting tumor spread and immune pathology. An alternative explanation, offered here, is that damage associated molecular pattern molecules, released in excess, maintain a local milieu associated with recruitment and retention of immune cells associated with failed lymphatic clearance and functional lymphatic obstruction. We found that levels of High mobility group box 1 (HMGB1) were equally elevated in both benign and malignant pleural effusions (MPE) and that limited diversity of T cell receptor expressing gamma and delta chain were inversely associated with these levels in MPEs. Acellular fluid from MPEs enhanced  T cell proliferation in vitro, while inhibiting cytokine production from  T cells and monocytes as well as restricting monocyte chemotaxis. Novel therapeutic strategies, targeting HMGB1 and its neutralization in such effusions as well as direct delivery of immune cells into the pleural space to reconstitute normal physiology should be considered.